2019
DOI: 10.1038/s41598-019-41993-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic resistance of the D-peptide RD2 developed for direct elimination of amyloid-β oligomers

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disorder leading to dementia. Aggregation of the amyloid-β peptide (Aβ) plays an important role in the disease, with Aβ oligomers representing the most toxic species. Previously, we have developed the Aβ oligomer eliminating therapeutic compound RD2 consisting solely of D-enantiomeric amino acid residues. RD2 has been described to have an oral bioavailability of more than 75% and to improve cognition in transgenic Alzheimer’s disease mouse models after oral admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…929 For other peptide-based inhibitors, readers are referred to a recent review 930 and recent articles. [931][932][933]…”
Section: Polymer-based Moleculesmentioning
confidence: 99%
“…929 For other peptide-based inhibitors, readers are referred to a recent review 930 and recent articles. [931][932][933]…”
Section: Polymer-based Moleculesmentioning
confidence: 99%
“…AMT has also been proposed for the transport of several arginine-rich peptides, such as the basic peptide derived from the human immunodeficiency virus type 1 (HIV-1) Tat proteins, across the BBB [50]. In extensive in vitro stability studies, we demonstrated that RD2 is remarkably resistant against metabolization in simulated gastrointestinal fluids, blood plasma and liver microsomes and shows no relevant human-specific metabolites [51]. Therefore, we concluded that it is perfectly suitable and safe for oral administration in humans.…”
Section: Consequences Of the Concept Of A Replicating Toxic Aβ Assmentioning
confidence: 99%
“…The head-to-tail tandem version of RD2, RD2RD2, was originally designed to obtain a bivalent version of RD2 with potentially higher avidity and affinity for polyvalent Aβ assemblies. Like RD2, also RD2RD2 belongs to a relatively new class of drugs, the all-D-peptides, which consist solely of D-enantiomeric amino acid residues and which exhibit several advantages including high proteolytic stability and low immunogenicity [37,38].…”
Section: Introductionmentioning
confidence: 99%